Foreign direct investment, a movement toward investors' centricity, a behavioral perspective - TAN, Jimmy Wee Teck (Institutional Knowledge at Singapore Management University, 2018)
This dissertation proposal studies the determinants of Foreign Direct Investment (FDI) in a frontier economy from the behavioral perspective of a manager. There are many determinants used in determining a Foreign Direct Investment. These determinants range from economic, social, institutional, technology, organization, and commercial down to cultural distance. The objective of this research is not to duplicate the methodologies of many quantitative research studies that have been conducted, in which many economists use quantitative analysis of several years of data to determine the many factors that correlate with levels of FDI. The behavioral aspect of a manager’s decision is noticeably absent in most economic models. This research study surveyed and interviewed managers to understand their mental calculus in making Foreign Direct Investment decisions. During our research, we conducted a preliminary exploratory survey of the various ways managers tend to make important decisions regarding Foreign Direct Investment. A semi-structured questionnaire and interviews were carried out with managers. This was done after the initial literature review, to understand the location, certainty and investment types of determinants they would consider when investing in Singapore, Vietnam, and Myanmar. The data obtained were analyzed, and with further literature review, we proposed several hypotheses. These hypotheses were to test the effect of the moderating determinants such as the culture, language, ethnic similarity, physical distance, economic policies, market opportunity and the legal system relationship between investors willingness to invest in two emerging economies; Vietnam and Myanmar. The legal system characteristics considered are legal clarity, legal transparency, legal corruption and legal enforcement. The results obtained will be useful to develop prescriptive advice to official and administrators in crafting Foreign Direct Investment policies in frontier economies.